Thoracic Outlet Syndrome Induced by Huge Lipoma: A Case Report - Sul, Junghoon (Korean J Neurotrauma, 2019)
Thoracic outlet syndrome is a relatively well known disease. Other than trauma, this disease is mostly caused by anatomical structures that cause vascular or neural compression. The cause of thoracic outlet syndrome is diverse; however, there are only few reports of thoracic outlet syndrome caused by lipoma in the pectoralis minor space. We report a case of compression of the lower trunk of brachial plexus in which a large lipoma that developed in the pectoral minor space grew into the subclavicular space, along with a review of literature.